Circular RNA CDR1as Alleviates Cisplatin-Based Chemoresistance by Suppressing MiR-1299 in Ovarian Cancer - Wu, Han; Zhao, Xibo; Wang, Jing; Jiang, Xinyan; Cheng, Yan; He, Yanan; Sun, Liyuan; Zhang, Guangmei (Frontiers in Genetics, 2022)
Cisplatin (CDDP) chemoresistance has seriously affected the prognosis and survival of ovarian cancer (OC) patients. Circular RNA CDR1as has established biological association with a great number of cancers. However, the molecular mechanism of CDR1as in CDDP chemoresistance OC remains unclear. Here, we explored the mechanism of CDR1as in CDDP resistance OC. Firstly, we employed bioinformatics analysis and quantitative real-time PCR (qRT-PCR) to determine the expression of CDR1as and related RNAs in CDDP sensitive and resistance OC tissues and cells. Then, the function experiments were used to determine cell proliferation, invasion, migration, and apoptosis in CDDP chemoresistance and parent OC cells in vitro. The effect of CDR1as in CDDP chemoresistance OC progression was tested in nude mice in vivo. Moreover, dual-luciferase assays and RNA immunoprecipitation (RIP) were performed to confirm the interactions of CDR1as and related RNAs. Finally, the protein expression levels were evaluated by western blot. In summary, we interpret the underlying mechanism of CDR1as/ miR-1299/ PPP1R12B axis and shed light on the clinical application for CDDP chemoresistance in OC.